2011
DOI: 10.1002/jez.b.21441
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic development of an exceptionally preserved Devonian cartilaginous skeleton

Abstract: Cartilaginous vertebrate skeletons leave few records as fossils, unless mineralized. Here, we report outstanding preservation of early stages of cartilage differentiation, present in the Devonian vertebrate Palaeospondylus gunni. In large specimens of Palaeospondylus, enlarged, hypertrophic cell spaces (lacunae) are dominant in the cartilage matrix, each defined by thin mineralized matrix, where phosphorus and calcium co-occur. This is comparable to living endochondral cartilage, where cell hypertrophy and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…These features, however, may have evolved from cyclostome-like conditions. The calcified cartilage of Palaeospondylus lacked perichondral ossification [ 48 ], which is specific to the gnathostomes [ 38 ], and it is conceivable that the calcified cartilage of Palaeospondylus evolved either through loss of perichondral ossification in gnathostomes, or through acquisition of biomineralization in cyclostomes. The latter possibility appears more plausible, as the hypertrophied cell lacunae in the cartilages of Palaeospondylus [ 11 , 48 ] are reminiscent of cyclostome cartilages in their thin layers of extracellular matrix [ 21 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features, however, may have evolved from cyclostome-like conditions. The calcified cartilage of Palaeospondylus lacked perichondral ossification [ 48 ], which is specific to the gnathostomes [ 38 ], and it is conceivable that the calcified cartilage of Palaeospondylus evolved either through loss of perichondral ossification in gnathostomes, or through acquisition of biomineralization in cyclostomes. The latter possibility appears more plausible, as the hypertrophied cell lacunae in the cartilages of Palaeospondylus [ 11 , 48 ] are reminiscent of cyclostome cartilages in their thin layers of extracellular matrix [ 21 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The calcified cartilage of Palaeospondylus lacked perichondral ossification [ 48 ], which is specific to the gnathostomes [ 38 ], and it is conceivable that the calcified cartilage of Palaeospondylus evolved either through loss of perichondral ossification in gnathostomes, or through acquisition of biomineralization in cyclostomes. The latter possibility appears more plausible, as the hypertrophied cell lacunae in the cartilages of Palaeospondylus [ 11 , 48 ] are reminiscent of cyclostome cartilages in their thin layers of extracellular matrix [ 21 , 49 ]. A recent study also suggested that the vertebral element is synapomorphic to the vertebrates [ 21 , 50 ], and the cylindrical vertebral column in Palaeospondylus (Additional file 1 : Figure S1) may have evolved secondarily from arcualia in basal cyclostomes, through the invasion of cartilaginous cells into the fibrous sheath within the elastica externa [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also problematic with regards to a chondrichthyan association is the composition of the Palaeospondylus cartilaginous skeleton that includes hypertrophied chondrocyte lacunae surrounded by mineralized matrix, previously interpreted as representing an early stage in endochondral bone development [ 10 , 47 ], a type of bone found in bony fishes (Osteichthyes) [ 48 ]. The presence of hypertrophied cells in chondrichthyan cartilage is disputed [ 49 , 50 ], with mineralization characteristically only in the perichondral tesserae [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fishes occur throughout several beds, with Palaeospondylus co-occurring with the lungfish Dipterus, the acanthodian Mesacanthus, and the placoderm Pterichthyodes [5]. Previously, Palaeospondylus has been assigned to almost every major jawless and jawed vertebrate group and identified as both larval and adult [6][7][8][9][10][11]. Most recently, Hirasawa et al [12] described similarities between Palaeospondylus and larvae of the extant hagfish Eptatretus burgeri, suggesting a hagfish affinity, and more particularly as a stem hagfish.…”
Section: Introductionmentioning
confidence: 99%
“…Also known to mineralize their matrix are the chondrocytes, not only at the ossification front of endochondral bone growth (in the case of hyaline cartilage), but also in stable forms of mineralized cartilage such as fibrocartilages and other forms of cartilage displaying striking similarities to bony tissues ( Beresford, 1981 ; Dyment et al, 2015 ; Paul et al, 2016 ; Pears et al, 2020 ; Berio et al, 2021 ). Even though both perichondral bones and cartilaginous tissues displayed mineralization in the earliest forms of mineralized internal skeletons ( Ørvig, 1951 ; Min and Janvier, 1998 ; Donoghue et al, 2006 ; Johanson et al, 2010 , 2012 ; Pears et al, 2020 ), mineralizing cartilages have been understudied from a genetic and evolutionary perspective in extant vertebrates. A better understanding of the genetic underpinning of the mineralizing chondrocytes is therefore necessary to understand the early steps of the evolution of endoskeletal mineralization in vertebrates.…”
Section: Introductionmentioning
confidence: 99%